THE IMPACT OF INNOVATIVE AND TRANSFORMATIONAL CHANGES ON THE ECONOMIC ACTIVITY OF YOUNG PEOPLE (Scientific journal of the Fergana State University, 2023)
The purpose of the research in this article was an attempt to reveal the specifics of innovative and transformational aspects of youth economic activity and its significance in the modern period of reforms.The article uses such research methods as an integrated approach, historicity and consistency, comparative analysis, observation, sociological survey.